B-Type Peptides to Predict Post-Liver Transplant Mortality: Systematic Review and Meta-Analysis - Chahal, Daljeet (2019)
Background & Aims: Cirrhotic patients undergoing liver transplantation are at high risk of death from cardiac complications. Brain Natriuretic Peptide (BNP) and Amino Terminal Brain Natriuretic Peptide (NT-BNP) are commonly utilized in cardiac risk stratification. Their significance in predicting mortality risk in cirrhotic patients during or after liver transplantation is unknown. We conducted a systematic review and meta-analysis to answer this question.Methods: An electronic search of EMBASE, MEDLINE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews (2005 to Sept 2016), Google scholar and study bibliographies was conducted. Study quality was determined, and demographic and outcome data were gathered. Random-effects meta-analyses of mortality based BNP/NT-BNP level or presence of post-transplant heart failure were conducted.Results: Seven studies comprising 2010 patients were identified. Demographics were similar between patients with high or low BNP or NT-BNP levels. Hepatitis C was the most prevalent etiology of cirrhosis (38%). Meta-analysis revealed a pooled relative risk of 3.1 (95% CI 1.9 ? 5.0) for post-transplant mortality based on elevated BNP or NT-BNP level. Meta-analysis also revealed a pooled relative risk of 1.6 (95% CI 1.3 ? 2.1) for post-transplant mortality if patients had demonstrated post-transplant heart failure.Conclusion: Our analysis suggests that early BNP or NT-BNP measurement may help in risk stratification and provides data on post-operative mortality in cirrhotic patients undergoing liver transplantation. Discriminatory thresholds appear to be higher in cirrhotic patients relative to prior studies in non-cirrhotics. However, the number of analyzed studies is limited and our findings should be validated further through larger, prospective studies.